Efficacy and safety of aliskiren combination therapy: a protocol for an umbrella review. Issue 3 (9th March 2021) - Shen, Jiantong; Feng, Wenming; Wang, Yike; Zhao, Qiyuan; Flavorta, Billong Laura; Lu, Jingya
Abstract : Introduction: Efficacy of aliskiren combination therapy with other antihypertensive has been evaluated in the treatment of patients with hypertension in recent systematic reviews. However, most previous reviews only focused on one single health outcome or one setting, none of them made a full summary that assessed the impact of aliskiren combination treatment comprehensively. As such, this umbrella review based on systematic reviews and meta-analyses is aimed to synthesise the evidences on efficacy, safety and tolerability of aliskiren-based therapy for hypertension and related comorbid patients. Methods and analysis: A comprehensive search of PubMed, EMBASE, Cochrane Library, CNKI published from inception to August 2020 will be conducted. The selected articles are systematic reviews which evaluated efficacy, safety and tolerability of aliskiren combination therapy. Two reviewers will screen eligible articles, extract data and evaluate quality independently. Any disputes will be resolved by discussion or the arbitration of a third person. The quality of reporting evidence will be assessed using the Assessment of Multiple Systematic Reviews V.2 tool tool. We will take a mixed-methods approach to synthesising the review literatures, reporting summary of findings tables and iteratively mapping the results. Ethics and dissemination: Ethical approval is not required for the study, as we would only collect data from available published materials. This umbrella review will be also submitted to a peer-reviewed journal for publication after completion. PROSPERO registration number: CRD42020192131.